Efeitos vasculares da sobrecarga aguda de frutose em ratas - Silva, Kevin Mesquita (2023)
INTRODUCTION: Fructose excessive consumption, mainly with the introduction of high fructose corn syrup by the food industry, has been associated with vascular alterations. The absorption and metabolism of fructose differs from glucose and is not subject to the same regulatory mechanisms, so fructose can be used as a substrate for de novo lipogenesis, a factor that contributes to the increase in lipid fractions that is associated with the development of cardiovascular diseases (CVD). CVD affects men and women differently and ovarian hormones are thought to have a protective effect on cardiovascular dysfunction. Although studies of chronic fructose consumption are well studied, the short-term effects of high fructose consumption have not yet been fully clarified. OBJECTIVE: To determine the effects of acute fructose overload on the vascular function of female rats submitted to ovariectomy or not. To describe the role of perivascular adipose tissue and endothelium in the contractile responses of rat aorta after 4 days of fructose overload. MATERIAL AND METHODS: Female Wistar rats (n=52) underwent ovariectomy (OVX) or sham surgery (SHAM). After recovery, they received a 10% (w/v) fructose solution (Fr) or water (Ct) for 4 days. Body weight, chow consumption and plasmatic glycaemia were measured. Afterwards, the thoracic aorta was dissected and cut into rings segments that were mounted in an organ bath to detect changes in arterial wall tension induced by increasing concentrations of the alpha1-adrenergic agonist, phenylephrine (Phe). Maximum responses (Rmax) and pD2 (-logEC50) to Phe were expressed as mean ± standard error of mean and compared using Student's t test and two-way ANOVA between groups, with p<0.05 considered statistically significant. RESULTS: Ovariectomy induced increase in chow consumption on Ct group. Fructose overload induced increase in weight gain in OVX group (ΔWeight: 12,10±1,99g) when compare to both SHAM Fr (ΔWeight: 7,13±1,01g) and OVX Ct (ΔWeight: 4,42±0,57g), also both ovariectomy and fructose treatment, alone, promoted increase in plasmatic glycaemia. Fructose overload reduced Rmax of OVX group (Rmax PVAT+/E+: OVX Ct 96,47±7,07 OVX Fr 65,44±3,00) in intact aorta segments. Without PVAT, fructose treatment resulted in a decrease in Rmax in both groups (Rmax PVAT-/E+: SHAM Ct 97,23±4,05 SHAM Fr 69,23±3,33 and OVX Ct 86,54±2,71 OVX Fr 72,51±2,61). These difference in the contractile responses of aortic rings without PVAT, were eliminated in the absence of endothelium (Rmax PVAT-/E-: SHAM Ct 141,53±4,63 SHAM Fr 135,81±7,03 and OVX Ct 138,04± 4,28 OVX Fr 146,16±7,70). Incubation with catalase revealed that hydrogen peroxide contraction modulation was exacerbated by fructose overload in both SHAM and OVX groups with intact aortic rings. In all groups, removal of the endothelium induced an increase in the contractile response, also incubation with L-NAME increase contractile response in all groups, but Fr groups showed no alteration in sensitivity. CONCLUSION: The results found indicate that fructose influences the anti-contractile modulation exerted by the PVAT and the endothelial layer in the contraction induced by Phe in isolated rings of the aorta of rats and ovarian hormones appear to have no influence over these alterations in vascular function promoted by 4 days of fructose overload. Furthermore, fructose consumption, even for short-time, was sufficient to increase weight gain and plasmatic glycaemia.